PENGOBATAN TRADISIONAL PADA MASYARAKAT DI DESA LEDE KABUPATEN PULAU TALIABU PROVINSI MALUKU UTARA - Rismawati Rismawati; Wa Ode Sifatu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study aims to describe the efforts made by the community in Lede Village to utilize the available treatment system. The theory that used to read research data is Foster & Anderson about health and healing. The method uses the collection of ethnographic data that emphasizes the ethical and emotional perspectives with involved observation techniques, in-depth interviews, explore information about the titles raised by the researcher. The results of this study indicate that the people of Lede Village tend to choose traditional medicine to deal with their pain. In the view of the local community that the disease experienced by the community in Lede Village was caused by occult spirits (posampa ako) or magic (personalistic) as well as diseases caused by unbalanced body conditions (naturalistic). The community's trust in treatment using the services of a healer (kampo pahekombi) tends to make people use more traditional medicine. In addition, it is also caused by equipment that is incomplete in public health services, as well as people's fears of chemical dependence.